2023
DOI: 10.1093/bioinformatics/btad495
|View full text |Cite
|
Sign up to set email alerts
|

CoCoNat: a novel method based on deep learning for coiled-coil prediction

Abstract: Motivation Coiled-coil domains (CCD) are widespread in all organisms and perform several crucial functions. Given their relevance, the computational detection of coiled-coil domains is very important for protein functional annotation. State-of-the art prediction methods include the precise identification of coiled-coil domain boundaries, the annotation of the typical heptad repeat pattern along the coiled-coil helices as well as the prediction of the oligomerization state. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…12,29 The predicted structures of Daed and Gasz showed that the second of the two α-helixes (Ala191– His235) of Daed roughly overlaps with the CC domain (Thr206–Ser234) and that the two α-helixes in Gasz (Phe345–Glu374 and Glu383–Ser412) are present between the SAM and TM domains (Figure 1C). The amino acid sequence-based prediction of the CC region 32 also roughly overlaps with the tandem α-helix regions (Figure S1A), supporting the AlphaFold2 prediction. We propose that the two tandem α-helixes present in both Gasz and Daed are referred to as extended coiled-coil (eCC) domains (Figure 1C).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…12,29 The predicted structures of Daed and Gasz showed that the second of the two α-helixes (Ala191– His235) of Daed roughly overlaps with the CC domain (Thr206–Ser234) and that the two α-helixes in Gasz (Phe345–Glu374 and Glu383–Ser412) are present between the SAM and TM domains (Figure 1C). The amino acid sequence-based prediction of the CC region 32 also roughly overlaps with the tandem α-helix regions (Figure S1A), supporting the AlphaFold2 prediction. We propose that the two tandem α-helixes present in both Gasz and Daed are referred to as extended coiled-coil (eCC) domains (Figure 1C).…”
Section: Resultssupporting
confidence: 67%
“…( A ) Sequence-based CC prediction of Daed (upper) and Gasz (lower) by CoCoNat. 32 Red line indicates the CC region predicted by AlphaFold2. ( B ) Western blotting shows that anti-Daed monoclonal antibodies produced in this study are specific to Daed.…”
Section: Supplemental Figure Legendsmentioning
confidence: 99%
“…2 ). According to 3 in silico coiled-coil structure prediction tools (CoCoNat, DeepCoil2, and CoCoPred) 33 35 , the variant was consistently predicted to disrupt the coiled-coil structure in CARD9 and thus be pathogenic (Supplementary Fig. 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…although this was not apparent at the CASP15 experiment (Simpkin, Mesdaghi et al, 2023). Also notable are the continued difficulties with coiled-coil proteins, whose unpredictable irregularities, oligomeric state and parallel vs antiparallel architectures remain, despite ongoing efforts (Madeo et al, 2023;Madaj et al, 2024), a significant hindrance to structure prediction and hence the use of modelled structures for MR.…”
Section: Discussionmentioning
confidence: 99%